(3GdJQZjH aj GdYQHjI hGdEYQGHs
(3ChdgG (B:s
(3GdMeO ddg hHg CSJYjf gPGcJGH GdJZQjH ai GdYQHjI hGdEYQGH bGd QShd Gddg Udi Gddg Ydjg hSde(B: (3LeGd GdQLd dSGfg (B" s
(3BNQgG (B:s
(3dhcfJ ef GdeGA cfJ eRfI Ch cfJ fLeG cfJ SYO GdSYhO Je GdJQZjH hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B89 - (3U(B91s
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs